2020
DOI: 10.1128/iai.00117-20
|View full text |Cite
|
Sign up to set email alerts
|

The Serratia marcescens Siderophore Serratiochelin Is Necessary for Full Virulence during Bloodstream Infection

Abstract: Serratia marcescens is a bacterium frequently found in the environment, but over the last several decades it has evolved into a concerning clinical pathogen, causing fatal bacteremia. To establish such infections, pathogens require specific nutrients; one very limited but essential nutrient is iron. We sought to characterize the iron acquisition systems in S. marcescens isolate UMH9, which was recovered from a clinical bloodstream infection. Using RNA sequencing (RNA-seq), we identified two predicted sideropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Siderophores are both considered critical pathogenicity factors for many humanassociated microbes (Weakland et al 2020) and are also known to facilitate interactions with other microbes and the innate immune system in the human gut microbiome (Behnsen and Raffatellu 2016;Holden et al 2016;Zhu et al 2020;Lam et al 2018). Therefore, being able to annotate genes for the production of siderophores across diverse bacterial species may be critical for understanding the distribution of virulence factors, yet it is difficult to do using traditional annotation pipelines alone.…”
Section: Discussionmentioning
confidence: 99%
“…Siderophores are both considered critical pathogenicity factors for many humanassociated microbes (Weakland et al 2020) and are also known to facilitate interactions with other microbes and the innate immune system in the human gut microbiome (Behnsen and Raffatellu 2016;Holden et al 2016;Zhu et al 2020;Lam et al 2018). Therefore, being able to annotate genes for the production of siderophores across diverse bacterial species may be critical for understanding the distribution of virulence factors, yet it is difficult to do using traditional annotation pipelines alone.…”
Section: Discussionmentioning
confidence: 99%
“…As homologous transporters have been characterized across Gram‐negative bacteria, it has become clear that these transporters play a large role in transporting many different macromolecules across the outer membrane that are too large to diffuse via porins. Because of this key role in nutrient uptake, TBDTs are often essential for sensing and adapting to environmental signals and are associated with pathogenicity in bacteria such as E. coli, Pseudomonas aeruginosa, and Serratia marcescens , among others (Takase et al., 2000; Torres et al., 2001; Weakland et al., 2020).…”
Section: General Features Of Tonb‐dependent Transportersmentioning
confidence: 99%
“…The iutA gene encoding the ferric aerobactin receptor involves typical ATP binding cassette (ABC)-type transporters. 54 The ferric uptake transporter encoded by kfu mainly mediates the uptake of ferric iron. 19 Previous study found that the highly virulent strains were more likely to carry the ferric ion carriers.…”
Section: Discussionmentioning
confidence: 99%